Prevalence of episodic headache in workers on different shifts in Brazilian industry - Ferreira, Pablo Guarisco; Ricardi, Lara Henriqueta Bussolaro; Santos, Mauricio Bedim dos; Cesar, Alcântara Ramos de Assis (Headache Medicine, 2024)
Introduction. Headache is one of the most prevalent and impactful clinical conditions globally. With varied estimates, there is currently a prevalence of up to 52% for episodic forms of headache in general, and 4.6% for chronic ones. Specifically, some studies indicate a global prevalence of 14% for migraine, of which only around 7% of these correspond to the chronic form, and 26% for tension-type headache (TTH). Smaller studies estimate a prevalence of 21.6% for frequent episodic TTH. As with chronic forms of TTH and migraine, sleep disorders are associated with their episodic forms, increasing the impact and frequency of attacks. Objective. To calculate the prevalence of frequent episodic headaches in workers from different shifts in an industry in Brazil, and evaluate the possible association with sleep disorders. Methods. This is an analytical cross-sectional observational study. The survey was carried out using an electronic form via the Google Forms® platform. Data regarding headache frequency, shift and work sector (production or others) and sleep were evaluated. Workers aged ≥ 18 years were included, who completely responded to the form and agreed to the free and informed consent form; Those reporting an age ≥ 51 years were excluded. Binary logistic regression was used to estimate the odds ratio (OR) and a 95% confidence interval was considered to express the degree of association between the independent variables. The research project was approved by the Research Ethics Committee of the Health Sciences Sector of the Federal University of Paraná. Results. 354 volunteers met analysis criteria. A prevalence of episodic headache of 52.82% was found, with no statistically significant difference between work shifts (p=0.949) or sector (p=0.569). Although a significant number reported increased sleep latency (42%), non-restorative sleep (59.4%) and daytime sleepiness (28.8%), these variables did not show a statistically significant association with episodic headache. Conclusion. The prevalence found of frequent episodic headache was higher than that described in the literature and was not associated with sleep disorders or work shifts.